ANALISIS PERHITUNGAN PPH PASAL 21 TERHADAP GAJI PEGAWAI TETAP PADA PUSKESMAS SAMBUTAN KECAMATAN SAMARINDA ILIR - Shaleh, Rahmad (EKONOMIA, 2012)
The background of this research the law on cutting and collection of tax on income by the taxpayer on income by individual taxpayers according to the Regulation of the Minister of Finance No.: 250/PMK.03/2008 of income tax received by employees up to at minimum wage or minimum wage county / city declared invalid. This resulted in excess deduction. The purpose of this study was to determine the income tax Article 21 of the District Health Center Samarinda Ilir Welcome.There are differences in the results of the analysis mentioned income tax calculation is based on Article 21 by the regional minimum wage rates to the Regulation of the Minister of Finance No.: 250/PMK.03/2008.Â Each taxpayer should bear what has become dependent and if the taxpayer has more than 2 (two) children , the third child and so are not included in the calculated dependents . Similarly, a taxpayer who has a husband / wife who both work but a different place then the only taxpayers bear the marital status alone . Taxpayers who have the status of TK ( Not Married ) where section 21 income tax withheld by the employer in the can of Income Tax laws and the reduction of income tax article 21 by the government ( including the non-taxable income based on the status of the taxpayer ) . Taxpayers who have K/1/0 marital status , where the income tax is calculated from section 21 of article 21 income tax deduction of income tax payable by Article 21 by the government ( including the non-taxable income ) based on marital status K/1/1 , where tax article 21 income is calculated using income tax article 21 income tax payable decreased by article 21 by which the taxable income that the government has included marital status and 2 (two) people person . Thus the author proposed hypothesis is accepted .Â